PENYULUHAN DAN PENGUATAN KARAKTER PANCASILA PADA SISWA SMK BUNDA AUNI KOTA BEKASI - Hanggono Arie Prabowo; Lengsi Manurung; Siti Alifah; Husain Nurisman; Luluk Setyowati; Dellia Mila Vernia; Sigit Widiyarto; Lidya Natalia Sartono; Nana Suyana (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
The growth and development of good character will encourage students to grow with the capacity and commitment to do things the best and do everything correctly and have a purpose in life. Based on this statement, schools as educational institutions have a responsibility to develop and strengthen character to produce students with character. Strengthening the character of Pancasila is important at this time, to answer the challenges of the times. This activity was attended by 30 vocational high school students from nursing and pharmacy study programs. The activities were carried out from January to March 2024. The results of the activities showed that the students were able to apply the Pancasila character attitudes, even though they were not yet spontaneous and routine